2018
DOI: 10.1080/07055900.2018.1514579
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Canada's Climate: Trends in Indices Based on Daily Temperature and Precipitation Data

Abstract: Trends in indices based on daily temperature and precipitation are examined for two periods: 1948-2016 for all stations in Canada and 1900-2016 for stations in the south of Canada. These indices, a number of which reflect extreme events, are considered to be impact relevant. The results show changes consistent with warming, with larger trends associated with cold temperatures. The number of summer days (when daily maximum temperature >25°C) has increased at most locations south of 65°N, and the number of hot d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
139
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(151 citation statements)
references
References 39 publications
11
139
0
1
Order By: Relevance
“…Conversely, 24 hr and longer‐duration AM will more likely occur earlier in the year (before July) in future climate and their seasonal variability is projected to increase for all durations, as the dates of AM occurrences are more dispersed around their summer peaks at the end of the simulation. Hence, more frequent warm meteorological conditions are likely to increase the probability of occurrence of intense precipitation events over an extended period of the year (e.g.,Vincent et al., ). The projected changes in annual cycle statistics showed a well‐defined spatial structure over the study domain.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, 24 hr and longer‐duration AM will more likely occur earlier in the year (before July) in future climate and their seasonal variability is projected to increase for all durations, as the dates of AM occurrences are more dispersed around their summer peaks at the end of the simulation. Hence, more frequent warm meteorological conditions are likely to increase the probability of occurrence of intense precipitation events over an extended period of the year (e.g.,Vincent et al., ). The projected changes in annual cycle statistics showed a well‐defined spatial structure over the study domain.…”
Section: Resultsmentioning
confidence: 99%
“…However, a period of 31 years is relatively short to detect statistically significant changes. Using different selection criteria and a different time period, Wang (2006) found that some areas of Canada experienced an increasing trend of freezing rain events over the 1953-2004 period.…”
Section: Resultsmentioning
confidence: 99%
“…Regionally, Stewart and Yiu (1993) examined near-0 • C conditions including their horizontal scales and associated precipitation over southern Ontario. In terms of associated precipitation, MacKay and Thompson (1969) published the first climatology of freezing precipitation for Canada, and this was later updated by Stuart and Isaac (1999) and Wang (2006). Many case study analyses of heavy precipitation and/or freezing rain events have been carried out to investigate storm structure and the associated precipitation production mechanisms (e.g., Henson et al, 2007Henson et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Canada's annual mean surface air temperature has warmed by 1.8°C over the period 1950-2016 (Vincent et al 2018), which is about twice that of the global mean temperature (0.85°C over the period 1880-2012IPCC 2014). Its warming rate is projected to continue to be faster than the global rate due to polar amplification (Li et al 2018).…”
Section: Introductionmentioning
confidence: 98%